The Translation of Figurative Languages in Novel Lelaki Harimau by Eka Kurniawan - Nurul Huda Gustema (Universitas Airlangga, 2020)
AbstractTranslation plays roles in providing access from various sciences and the latest technology, literature, religion, and culture. Novel is one of literary works that is translated into several languages. In a novel, there are some new culture-specific items, arts, and the figurative language that come from the source language. This research aimed to identify the translation of figurative languages in novel Lelaki Harimau by Eka Kurniawan which had been translated into English as Man Tiger by Labodalih Sembiring. From the translation of the title, it had revealed that the novel contains figurative languages. Therefore, the researcher aimed to examine the strategies and the ideology used in translating the figurative languages contained in the novel. This research implemented decriptive qualitative method, by using reading and note taking technique. A parameter to determine which words or phrases belong to figurative language was used as the instrument. Then, the result showed that the strategy that mostly used was literal translation, and domestication as the translation ideology.Keywords: figurative language, Lelaki Harimau, Man Tiger, translation.